Situational Variability of Means of Expression of Positive Emotions in Modern English (Proceedings of Southern Federal University. Philology, 2017)
Alina K. Kisil (Southern Federal University, Rostov-on-Don, Russian Federation)The article investigates situational variability of  means of expression of positive emotions in Modern English. This problem is topical for linguistics of emotions, pragma- and sociolinguistics. The author analyzes verbal, paraverbal and nonverbal  means of expressing positive  emotions of joy and surprise in three communicative registers: official, neutral and unofficial. These registers are singled out  on the basis of situational context and participants of the situation. The investigation gave the author the opportunity to come to the conclusion that in  the official register emotions are controlled and very often are subject to strategic purposes. They implement the upgrading strategy the aim of which is to give a high evaluation of  the addressee and of everything what is happening. It stipulates the use of corresponding expressive words and word combinations, exclamatory sentences, repetitions and rhetorical questions. Paraverbal means include  only light laughter and nonverbal –  a smile,  the expression of the eyes,  nods and tangled breath. The range of the means in question is wider in the neutral register where the speaker can use such verbal means as interjections with long sounds, expletives, pauses, descriptions of own emotions. Such paraverbal means as the emotional color of the voice and its volume, intonation, different kinds  of laughter and such nonverbal means as different kinds of smile, the expression of the face, gestures and movements are also used. Unofficial register is especially rich in means of expressing  positive emotions. Besides means typical of other registers such verbal means as obscene lexicon, phrasal words and graphical means are used here. Paraverbal means include numerous verbs reflecting  the volume of voice and nonverbal – rich mimic, friendly hugs and kisses.Key words: emotions, emotionality, joy, surprise, situational varieties, official, neutral, unofficial register, verbal, paraverbal, nonverbal  means, upgrading strategy DOI 10.23683/1995-0640-2017-2-85-94